2013
DOI: 10.1186/1471-2369-14-35
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of mitochondrial DNA 5178 C/A polymorphism and alcohol consumption on estimated glomerular filtration rate in male Japanese health check-up examinees: a cross-sectional study

Abstract: BackgroundPrevention of chronic kidney disease (CKD) is a major public health issue. Although several studies have been performed on the association between alcohol consumption and CKD or renal function, it remains controversial. Numerous genetic polymorphisms have been reported to be associated with CKD and kidney function. Mitochondrial DNA cytosine/adenine (Mt5178 C/A) polymorphism is associated with longevity in Japanese. This polymorphism modifies the effects of alcohol consumption on blood pressure, risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…Some studies in the general population have reported that alcohol consumption is inversely associated with the renal dysfunction or the incidence of chronic renal disease [10,11,12,13,14], whereas others have reported that alcohol consumption is positively related to renal impairment [15,16], or that there is no relationship between alcohol consumption and renal function [14,17,18]. Furthermore, there were no studies on alcohol consumption and renal function in Korean population, and the results of previous studies in other populations may be difficult to generalise to Korean populations due to ethnic differences[10,15,16,17,18,19,20] or dissimilar population subgroups [11,12,18]. The lack of evidence about the influence of alcohol drinking on renal function has limited the use of controls on alcohol drinking as a method for preventing and monitoring the progression of renal insufficiency.…”
Section: Introductioncontrasting
confidence: 40%
“…Some studies in the general population have reported that alcohol consumption is inversely associated with the renal dysfunction or the incidence of chronic renal disease [10,11,12,13,14], whereas others have reported that alcohol consumption is positively related to renal impairment [15,16], or that there is no relationship between alcohol consumption and renal function [14,17,18]. Furthermore, there were no studies on alcohol consumption and renal function in Korean population, and the results of previous studies in other populations may be difficult to generalise to Korean populations due to ethnic differences[10,15,16,17,18,19,20] or dissimilar population subgroups [11,12,18]. The lack of evidence about the influence of alcohol drinking on renal function has limited the use of controls on alcohol drinking as a method for preventing and monitoring the progression of renal insufficiency.…”
Section: Introductioncontrasting
confidence: 40%
“…Further, mtDNA haplogroups J and V have been associated with reduced susceptibility to chronic renal allograft dysfunction in comparison to haplogroup H 31 which has also been associated with a higher risk of the development of post-renal transplant diabetes 32 . Finally, a gene-environment interaction study suggested an association between the longevity-associated mt5178A genotype, regular alcohol consumption and better renal function in non-diabetic Japanese men 33 .…”
Section: Discussionmentioning
confidence: 97%
“…Green tea consumption was classified based on the number of cups of green tea per day (≤ 1 cup per day, 2–3 cups per day, 4–5 cups per day, and ≥ 6 cups per day). Selection of these lifestyle habits was based on previous research [15, 16, 21].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple logistic regression analysis was conducted to calculate odds ratios (ORs) for the risk of reduced eGFR. Reduced eGFR was defined as < 90 mL/min/1.73 m 2 [15, 16, 24–26] or < 75 mL/min/1.73 m 2 [27]. For simple and multiple linear regression analyses, age (< 50 years = 1, 50–59 years = 2, ≥ 60 years = 3), habitual smoking (never- or ex-smokers = 0, 1–20 cigarettes smoked per day = 1, ≥ 21 cigarettes smoked per day = 2), alcohol consumption (non- or ex-drinkers = 0, occasional drinkers = 1, daily drinkers = 2), green tea consumption (≤ 1 cup per day = 1, 2–3 cups per day = 2, 4–5 cups per day = 3, ≥ 6 cups per day = 4), and antihypertensive treatment (not receiving antihypertensive treatment = 0, receiving antihypertensive treatment = 1) were numerically coded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation